Bacteriophage treatment of Campylobacter biofilms : formation of the carrier state life cycle - Siringan, Patcharin (2013)
Campylobacter jejuni is a gram-negative thermotolerant microaerobic pathogen that causes human gastroenteritis worldwide. The production of extracellular polymeric substances to create a biofilm is a mechanism by which C. jejuni can protect itself from unfavourable environments, and is a contributory factor to the survival and transmission of the organism to farms animals and into the human food chain. Bacteriophages are natural predators of bacteria that have the potential for use as targeted biocontrol agents with the advantage that they can penetrate and affect bacteria embedded in biofilms. The effects of virulent Campylobacter-specific bacteriophages CP8 and CP30 on C. jejuni biofilms formed on glass by strains NCTC 11168, PT14 and HPC5 at 37 °C under microaerobic conditions were investigated. Independent bacteriophage treatment led to 1 to 3 Log10 CFU/cm2 reductions in the viable count 24 h postinfection compared with control levels. In contrast, bacteriophage applied under these conditions effected a reduction of less than 1 Log10 CFU/ml in planktonic cells. Resistance to bacteriophage in bacteria surviving bacteriphage treatment of C. jejuni NCTC 11168 biofilms was >80%, whereas bacteriophage resistance was not found in similarly recovered C. jejuni PT14 cells. Concomitant dispersal of the biofilm matrix by bacteriophage was demonstrated by crystal violet staining and transmission electron microscopy (TEM). The resistant survivors of bacteriophage treatment of biofilms formed by HPC5 and PT14 remained closely associated with the phage but not NCTC 11168. Analysis of the DNA contents of these isolates by PFGE and Southern transfer confirmed the presence of phage genomic DNA (approximately 140 kb) leading to the conclusion that these strains represent examples of the carrier state life cycle (CSLC) reported for other bacterial species. TEMs of CSLC cultures demonstrated the association of bacteriophage particles with Campylobacter cells that were devoid of flagella. Physiological studies of the CSLC strains showed the bacteria were non-motile but able to grow at a similar rate to parental cultures until reaching the phage proliferation threshold (7 Log10 CFU/ml) when growth rate declined and the phage titre increased. Of further note the CSLC strains had a greater capacity to survive atmospheric oxygen under nutrient limited conditions. CSLC phages exhibited differences in host binding, efficiency of plating and host range. Transcriptome analyses of CSLC strains harvested from microaerobic cultures at early exponential phase prior to phage proliferation were performed using DNA microarrays to demonstrate changes in host gene expression as compared with parental cultures. Notably genes involved in metabolism and the modification of macromolecules were up-regulated and specific flagella biosynthesis functions down-regulated in the CSLC strains.